Coordination of Planning in the Use of General Allocation Funds for Regional Civil Servant Salaries by the Regional Finance Service of Indramayu Regency - Ismanudin (Penerbit Hellow Pustaka, 2025)
This study aims to determine and understand the coordination of planning in the use of General Allocation Funds (DAU) for PNSD salaries by the Regional Finance Service of Indramayu Regency. The research method used is a descriptive method with a case study approach in qualitative research. The results of this study illustrate that the implementation of planning coordination based on the dimensions of coordination includes aspects: (a) clarity of authority and responsibility, (b) supervision and observation, (c) communication facilities, and (d) the ability of SKPD leaders that all of these aspects are quite good. However, there are still several constraints in the implementation of planning coordination, including the limited facilities and infrastructure for coordinating the management of finance from DAU revenues, including in the coordination aspect, both vertically, horizontally and diagonally. Efforts to overcome these obstacles include conducting coordination, both internally at the SKPD level and coordination with related cross-agency/agency.